Analysis Of Factors That Influence The Occurrence Of Audit Delay - Khoirunisa, Shinta Tharwiah; Sundarta, M. Imam (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2023)
The purpose of this study is to examine the effect of firm size, profitability, and KAP size on audit delays for consumer goods industry listed on the Indonesia Stock Exchange in 2019-2021. This study uses secondary data and the sample was obtained using a purposive sampling method, with a total sample of 48 companies. The research method used is multiple linear regression by using IBM SPSS program version 22. From the test results it is known that the coefficient value (R Square) is 0.467, which shows that profitability, firm size, and KAP size can explain audit delay of 46.7% and the residue 53.3% is other factors not include in this study. Based on the partial test, it can be concluded that profitability and KAP size have a negative and significant effect on audit delay. Meanwhile, firm size has no effect on audit delay. Where the size of the company does not affect the audit process carried out by the auditor, because the auditor does his work in accordance with the Public Accountant Professional Standards.